Relation of functional echocardiographic parameters to infarct scar transmurality by magnetic resonance imaging - Rost, Christian; Rost, Marie-Charlotte; Breithardt, Ole A.; Schmid, Michael; Klinghammer, Lutz; Stumpf, Christian; Daniel, Werner; Flachskampf, Frank A. (Journal of the American Society of Echocardiography, 2014)
Identification of viable but dysfunctional myocardium after myocardial infarction is important for management, including the decision for revascularization. Assessment of infarct transmurality (TRM) by late contrast enhancement on magnetic resonance imaging (MRI) is frequently used for this task but has several limitations, particularly its availability. The goal of this study was to compare the value of several simple echocardiographic parameters measured at rest at the bedside for the identification of three degrees of infarct TRM, with contrast-enhanced MRI as the gold standard.In a prospective, single-center study, 41 patients (33 men; mean age, 62 ± 10 years; 32 with ST-segment elevation infarctions) underwent resting echocardiography and contrast-enhanced MRI <5 days after infarction. Wall motion score, preejection velocity by tissue Doppler, and longitudinal, circumferential, and radial peak systolic strain by speckle-tracking-based strain imaging were assessed, and the findings were compared with infarct TRM stratified by contrast-enhanced MRI (no scar, 0% TRM; nontransmural scar, 1%-50% TRM; and transmural scar, 51%-100% TRM).Four hundred segments showed no scar, 125 showed nontransmural scar, and 213 showed transmural scar on contrast-enhanced MRI. The sensitivity and specificity of visual wall motion scoring to detect any scar versus no scar were 71% and 81%, respectively, similar to values for circumferential strain (sensitivity and specificity both 81% with a cutoff of -14.5%). Longitudinal and radial strain performed less well, and the presence of preejection velocity performed distinctly worse (45% and 90%, respectively). The sensitivity and specificity for identifying nontransmural versus transmural infarction was better for circumferential strain (78% and 75%, respectively, with a cutoff of -10.5%) than for the other strain types, preejection velocity (52% and 67%, respectively), or visual wall motion scoring (50% and 81%, respectively, for a score > 2).Visual wall motion analysis alone is able to detect infarcted myocardium but cannot differentiate sufficiently between transmural and nontransmural infarction. This is best achieved at the bedside using speckle-tracking-based circumferential strain.
EVALuna2:11951